Technology Acceptance of an Online Learning Platform: A Case Study of Leson.id - Astari Retnowardhani, Ailsa Amelia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This case study aims to evaluate e-learning acceptance through the modified UTAUT model by contributing variables to the acceptance of e-learning called Leson.id which developed by PT. Gramedia Widiasarana Indonesia. Leson.id site seeks to optimize user engagement through the features available on Leson.id. The purpose of this study is to evaluate the features of question processing and learning. .id by looking at the influence of independent variables on Behavior Intention and the influence of Behaviour Intention on Use Behaviour. The research was conducted using a modified UTAUT method. The data were collected through 35 questionnaire questions distributed to 392 leson.id users who had used the question processing and learning features on the Leson.id site. Based on the results of data processing using the PLS-SEM method through the smartPLS v.3.3.1 application, variables that greatly contributed to the higher e-learning acceptance were Performance Expectancy, Facilitating Condition, Effort Expectancy, Social Influence, and Price Value have a significant positive effect on Behaviour Intention; Self Efficacy and Anxiety have lower effect on Behaviour Intention; Behaviour Intention has a significant positive effect on Use Behavior.